Prediscussion and Postdiscussion Assessment Scores in a Self-Directed Learning Module Implemented in the Department of Biochemistry: A Comparative Study - Poonam Agrawal; Niket Verma (Indian Journal of Medical Specialities)
Background: Self-directed learning (SDL) is an important tool for transforming medical students into lifelong learners so that they are competent to identify their learning needs, allocate resources, and evaluate the learning process throughout their career. Recently, the Medical Council of India has introduced SDL as an essential component of the competency-based medical education curriculum and has allocated fixed hours for SDL in all undergraduate MBBS students. Regarding the role of facilitators in SDL program, there are controversial reports and there are even studies which have shown that the role of a facilitator is not important. Aim: The proposed study aimed to assess students' performance before and after discussion in an SDL module in small-group teaching–learning method and compare the performance scores. Methodology: A total of 117 students responded and were included in the study. Batch A had 59 students and Batch B had 58 students. The topic selected for the SDL module was “Heme degradation and Jaundice.” The module was conducted over two contact sessions, Session 1 and Session 2, which were conducted 5 days apart. The prediscussion and postdiscussion assessment questionnaire was also prepared. Session 1 was conducted during a 1-h SDL slot. A gap of 4 days was given to students for doing self-study and to learn the topic. The prediscussion questionnaire consisting of five multiple-choice questions related to the topic was shared with the students a day before the second contact session. Session 2 was conducted during the 2-h tutorial slot (over 2 consecutive days for two batches of the class, Batch A and Batch B, respectively). Fishbowl method of small-group teaching–learning was done followed by postdiscussion questionnaire. Results: The questionnaire was analyzed, and it was observed that the overall mean performance of students improved considerably (78.3%–87.7%) in the questions related to core concept (Q1, Q2, and Q3). Similarly, in the questions related to clinical aspects of the topic, the mean performance of students showed considerable improvement from prediscussion to postdiscussion assessment (86%–93.5%). Conclusion: We conclude that the SDL module should be meticulously planned keeping in mind the topic selected and the availability of infrastructure and workforce. Peer discussion is a very important aspect of the SDL module, and it shows improvement in learning outcomes in an SDL module.